Short interview with local fisherman in Bintulu, Sarawak on monthly income based on their experience - Abd Hamid, Izzah; Wan Yahaya, Wan Asrina; Rahim, Hairazi (Secholian Publication, 2022)
Fishermen earn income from their fishing activities, but it depends on various factors such as the type of employment, either part-time or full-time. The aim of the study is to identify which criteria based on their experience affect the income of part-time and full-time fishermen in Bintulu, Sarawak, Malaysia. About 33 fishermen were interviewed in the Bintulu area using semi-structured interview questions. A qualitative method such as an in-depth interview was conducted and analysed, resulting in three criteria that affecting our participants’ income. The first criterion was self-learning process which significantly hampered their ability to identify fish population areas, especially without the aid of technology. In contrast, the second criterion was equipment ownership. The ownership offers advantages to the full-time fisherman to facilitate their fishing activity by catching more fish in a short period of time. The final criteria were end products related to their sales activities, whether through intermediary (middleman) or directly to consumers. Regardless of their mode of operation or experience, direct-to-consumer sales is an alternative to earn a higher income, except that their yield varies significantly through the first and second criteria. Therefore, this finding indicated that the income of part-time or full-time fishermen in Bintulu, Sarawak could be influenced by three criteria.